(untitled) (Asian Business Research, 2024)
Downsizing is an organizational strategy used to reduce costs and improve performance to remain competitive. It is used by organizations to survive and adapt to changing market demands. The method used was to review thirty articles from well-recognized and highly ranked journals. The review process aims to gather all the factors and strategies of organizational downsizing from previous researches and articles between the years 1980 to 2019. The paper advances a deeper understanding of staff downsizing and addresses theoretical and methodological issues pertaining to the literature. The literature review assembled under the process of reviewing in the area of organizational downsizing and its impact on occupational stress and organizational commitment in these articles. After reviewing these papers, the findings gathered will be useful for organizations and employees.